Factores asociados y decisión de compra de medicamentos en usuarios de las boticas de Villa El Salvador – Lima 2021 - Guzmán Cuno, María Lourdes (Universidad Privada de Huancayo Franklin Roosevelt, 2021)
El estudio se realizó para determinar los factores asociados y decisión de compra de medicamentos en usuarios de las boticas Two Farma de Villa El Salvador - Lima 2021, siendo la metodología, transversal, prospectivo y observacional, en una muestra 100 usuarios que acudieron a la botica. Resultados, respecto a los factores asociados a la compra de medicamentos resultaron ser adecuados en un 100% y a la decisión de compra de medicamentos resultó ser apropiados en el 100%.; concluyéndose, los factores asociados a la compra de medicamentos son adecuados en el 100% y la decisión de compra de medicamentos son apropiados en un 100%

The study was conducted to determine the factors associated with and the decision to purchase medicines in users of the Two Farma drugstores in Villa El Salvador - Lima 2021, using a cross-sectional, prospective and observational methodology, in a sample of 100 users who went to the drugstore. Results: 100% of the factors associated with the purchase of medicines were adequate and 100% of the factors associated with the decision to purchase medicines were appropriate; it was concluded that 100% of the factors associated with the purchase of medicines were adequate and 100% of the factors associated with the decision to purchase medicines were appropriate
Associated factors and drug purchase decision in drug store users in Villa El Salvador - Lima 2021
Keywords: Factores asociados; Decisión de compra; Medicamentos; Usuarios; https://purl.org/pe-repo/ocde/ford#3.01.05